Site-Specific Enzymatic Activation of the Anti-HIV Agent Stampidine - Venkatachalam, Taracad K.; Qazi, Sanjive; Uckun, Fatih M. (Arzneimittelforschung, 2006)
Stampidine (STAMP, DDE-113, HI-113, N-[p-(4-bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine methyl ester, CAS 217178-62-6) and two stampidine analogs containing ethyl or t-butyl groups were synthesized and their rates of enzymatic activation were compared side-by-side. Enzymes such as lipase, esterase and protease did not hydrolyze the butyl substituted STAMP analog. These experimental results show that the site of attack for the enzymatic hydrolysis of STAMP is the ester side chain of the molecule.
Keywords: Anti-HIV agents; Antiretroviral therapy; N-[p-(4-Bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine methyl ester; CAS 217178-62-6; DDE-113; HI-113; Stampidine, enzymatic activation